Probability Weighting and Input Use Intensity in a State-Contingent Framework - Stein T. Holden; John Quiggin (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2017)
Climate risk represents an increasing threat to poor and vulnerable farmers in drought-prone areas of Africa. This study assesses the fertilizer adoption responses of food insecure farmers in Malawi, where Drought Tolerant (DT) maize was recently introduced. A field experiment, eliciting risk attitudes of farmers, is combined with a detailed farm household survey. A state-contingent production model with rank-dependent utility preferences is estimated. Over-weighting of small probabilities was associated with less use of fertilizer on all maize types and particularly so on the more risky improved maize types.
Keywords: C93; D03; O33; Q12; Q18; 330; Climate risk; state-contingent production; subjective probability weighting; technology adoption; adaptation; maize; Drought Tolerant maize; fertilizer use